Disenchantment, skepticism, and the early modern novel in Spain and France - Delehanty, Ann T., author.
1 online resource (viii, 173 pages).
Keywords: "This volume examines five early modern novels from the seventeenth century in Spain and France as examples of literature as a form of skeptical inquiry: Cervantes's Don Quijote, Zayas's Desengaños amorosos, Scarron's Roman comique, Cyrano de Bergerac's L'Autre Monde, and Mme. de Lafayette's Zayde. Due to its interdisciplinary nature, Disenchantment, Skepticism, and the Early Modern Novel in Spain and France appeals to literary scholars and intellectual historians of the early modern period in Europe, as well as advanced undergraduates and postgraduates studying the early novel, intellectual history, and philosophy of literature"--